TRANSFORMATION OF RELIGIOUS LEARNING FOR THE DEAF AND SENSORY DISABLED IN THE REALIZATION OF INCLUSIVE SOCIAL CHANGE - Eka Desi Susanti; Dewi Fitriyanti Sulistyaningrum (UNIVERSITAS SEBELAS MARET (UNS), 2025)
This research examines the transformation of religious learning for deaf people through the Deaf Recitation Movement initiated by PPA Darul Qur'an. This research aims to analyse four main aspects: the religious learning methods and curriculum applied, the challenges faced in the learning process, the social impact of this learning approach, and social reflection and comparison of inclusive education contexts in other countries. This research emphasises the importance of empowerment programs to provide equal access to religious education for people with disabilities, especially deaf people. The research results show that the Deaf Recitation Movement program has impacted inclusive social change. Even though it is faced with challenges, this program can increase independence and religiousness for people with disabilities